Radix Entomolaris in mandibular molars: An Endodontic Challenge - Chowdhury, Shirin Sultana; Hasan, Md Nazmul (Update Dental College Journal, 2014)
Mandibular molars can have additional root located lingually) the radix entomolaris). If present, an awareness and understanding of this unusual root canal morphology can contribute to the successful outcome of root canal treatment. The root is typically smaller than the distal root and is usually curved, requiring special attention when root canal treatment is being considered for such a tooth. The aim of the paper is to present a case of permanent mandibular first molar with additional third root. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21175 Update Dent. Coll. j: 2014; 4 (1): 49-52